Effect on growth performance and nutritive value of cultivated azolla filiculoides as an alternative feedstuff for ruminant - Hamidan, Mohammad Fitri Rimi; Mohd Nadzir, Mohd Noor Hisham; Shohaimi, Shamarina; Bidin, Habsah; Samat, Noraini (Penerbit Universiti Sains Malaysia, 2024)
Azolla filiculoides is a tiny, free-floating aquatic fern and has a potential alternative protein and fibre source for ruminants, was investigated for its cultivation optimisation and feedstuff suitability. Study 1 was conducted to investigate the influence of different fertiliser types (control, broiler manure, sheep manure, cow manure) and concentrations (0.25 g/L–1.25 g/L) on the growth performance (fresh weight, doubling time, relative growth rate) and nutrient composition (dry matter, ash, crude protein, crude fibre, crude fat) of A. filiculoides. The optimised type of fertiliser and concentration in Study 1 were further adopted in Study 2 to evaluate the effect of different fertiliser processing methods on the growth performance, nutritive value and in vitro rumen digestibility of A. filiculoides upon cultivation. The findings in Study 1 showed that cultivation of A. filiculoides using sheep manure at the concentration of 1.00 g/L is the best resulted in the shortest doubling time (3 to 5 days) and produced fresh weight (FW), relative growth rate (RGR), crude protein (CP) and crude fibre (CF) at 132.2 g/m2, 0.32 g/g/day, 21.2% DM-1 and 14.4% DM-1, respectively. Furthermore, unprocessed sheep manure (T3) exhibited superior (p < 0.05) fresh weight, relative growth rate, nutrient composition and fibre components compared to the burned manure treatment (T2). In vitro digestibility analysis discovered that T3 achieved a 24-hour accumulated gas production of 86.9 mL DM-1, with in vitro dry matter digestibility (IVDMD), in vitro organic matter digestibility (IVOMD) and metabolisable energy (ME) of 82.9%, 43.7% and 5.8 MJ/kg DM, respectively. These findings suggest that Azolla filiculoides cultivation can be economically optimised using 1.00 g/L unprocessed sheep manure (fresh manure), potentially serving as a self-produced, nutritious feedstuff for ruminants.